Does External Debt Worsen Environmental Pollution? Evidence from Morocco - Bachegour, Hikma; Qafas, Ahlam (International Journal of Energy Economics and Policy, 2023)
Morocco’s new development model report published in 2021 offers a renewed vision of the country's economic emergence strategy. It advocates an economic growth model that respects the environment and takes into consideration climate change challenges while promoting external debt, as one of the main economic instruments to achieve this new development pathway. This study investigates the empirical relationship between external debt and carbon dioxide emissions as an indicator of environmental pollution through the environmental Kuznets theory. As Morocco has a growing external debt and relies mainly on fossil fuels, the purpose is to analyze the long-term and short-term effect of external debt on carbon dioxide emissions using an ARDL model over the period 1984-2018. The time series data was collected from World Bank. The core findings of the study confirm the existence of inverted U-shaped Kuznets curve, they also reveal that external debt has a significant negative effect on carbon dioxide emissions in Morocco.